2020
DOI: 10.5194/angeo-2020-56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electron precipitation characteristics during isolated, compound and multi-night substorm events

Abstract: Abstract. A set of 24 isolated, 46 compound and 36 multi-night substorm events from the years 2008–2013 have been analysed in this study. Isolated substorm events are defined as single expansion-recovery phase pairs, compound substorms consist of multiple phase pairs, and multi-night substorm events refer to recurring substorm activity on consecutive nights. Approximately 200 nights of substorm activity observed over the Fennoscandian Lapland have been analysed for their magnetic disturbance magnitude and the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to them, although the diffuse electron precipitation at keV-10 keV energies provides a major contribution to the precipitated energy flux during substorms, observationally, it is limited within the 22-09 MLT sector, and its intense part does not propagate past the 06 h MLT meridian. Partamies et al, 2021 have shown that high energy electron tens-hundreds keV tends to be observed during the recovery phase of substorm, while during expansion phase electron energy is between few -10 keV. The depletion of keV-tens keV particle flux could most probably be explained by their precipitation losses.…”
Section: Discussionmentioning
confidence: 98%
“…According to them, although the diffuse electron precipitation at keV-10 keV energies provides a major contribution to the precipitated energy flux during substorms, observationally, it is limited within the 22-09 MLT sector, and its intense part does not propagate past the 06 h MLT meridian. Partamies et al, 2021 have shown that high energy electron tens-hundreds keV tends to be observed during the recovery phase of substorm, while during expansion phase electron energy is between few -10 keV. The depletion of keV-tens keV particle flux could most probably be explained by their precipitation losses.…”
Section: Discussionmentioning
confidence: 98%
“…The advantage of using Delaunay triangulation to map the data is that it can capture small‐scale features such as substorm activity that would be averaged out in other data sets. There is a disadvantage in that substorm activity will effectively persist for a day at a time since the maps have 1‐day resolution; in reality, these storms most likely have durations of minutes to hours (Beharrell et al., 2015; Cresswell‐Moorcock et al., 2013; Partamies et al., 2021). On the other hand, it is likely that not all substorms are observed, particularly in a year like 2003 when only three POES satellites were operational.…”
Section: Methodsmentioning
confidence: 99%
“…Thus there is increasing evidence that magnetospheric substorms, which are known to enhance chorus activity, lead to significant EEP into the atmosphere (Beharrell et al., 2015; Partamies et al., 2021). There is also evidence that multiple substorms should lead significant decreases in magnetospheric ozone (Seppälä et al., 2015), caused by substorm‐triggered EEP spanning a wide range of magnetic latitudes (Cresswell‐Moorcock et al., 2013).…”
Section: Introductionmentioning
confidence: 99%